Aging of polyvinylidene fluoride (PVDF) ultrafiltration membrane due to ozone exposure in water treatment: Evolution of membrane properties and performance. (December 2022) - Li, Kai; Xu, Weihua; Wen, Gang; Zhou, Zhipeng; Han, Min; Zhang, Shujia; Huang, Tinglin
Abstract: Pre-ozonation is an effective pretreatment tactic for mitigating fouling of ultrafiltration (UF) membrane in water and wastewater treatment, but the compatibility of polymeric UF membranes with residual ozone remains unclear. In this study, effects of long-term ozone exposure on properties and performance of polyvinylidene fluoride (PVDF) UF membrane reinforced by polyethylene terephthalate (PET) layer were systematically investigated. The exposure intensities were designed to simulate ozone exposure at 0.1 mg/L for 0.5–5 years. Chemical composition analysis suggested that the hydrophilic additives, such as possibly polyvinyl pyrrolidone (PVP), was gradually degraded and released from the membrane, whereas the PVDF matrix exhibited fairly good ozone resistance. Ozonation resulted in increase of pore size and decrease of surface hydrophilicity, which can be attributed to oxidation and dislodgement of hydrophilic additives. Accordingly, long-term ozonation led to moderate changes in performance factors, including increase of membrane permeability by 34%, decrease of retention ability by 21.8%, increase of organic fouling propensity. It is worth noting that membrane tensile strength suffered substantial decrease after ozonation, probably due to ozonation of the PET support layer. Overall, it seems that the PVDF functional layer exhibited good ozone resistance, but the PET support layer was the Achilles' heel of the reinforced PVDF membrane for integrating with pre-ozonation. Graphical abstract: Image 1 Highlights: Ozone resistance of a PVDF UF membrane with polyethylene terephthalate (PET) support layer was investigated. Ozonation led to oxidation and release of additives, but exerted minor influence on PVDF. Ozonation resulted in some decrease of retention ability and membrane resistance. PET was seriously degraded by ozone, leading to severe reduction of mechanical strength. Ozonated membranes exhibited higher fouling propensity due to enhanced foulants-membrane interactions.